Passavant's ridge during speech production with and without pharyngeal bulb - de Almeida, Beatriz K.; Ferreira, Gabriela Z.; Aferri, Homero C.; Marino, Viviane C.C. [UNESP]; Dutka, Jeniffer de C.R.; Pegoraro-Krook, Maria Inês (Elsevier, 2019)
The objective of this study was to investigate the occurrence of Passavant's ridge in patients with history of cleft palate presenting with velopharyngeal insufficiency (VPI) after primary palatal surgery. Twenty-five adult patients (mean age of 32 years), who wore a pharyngeal bulb prosthesis to correct VPI after primary palatoplasty participated in the study. Presence of Passavant's ridge was investigated in four conditions: prior to pharyngeal bulb for treatment of VPI (C1); during the molding of the pharyngeal bulb (C2); six months after the use of the pharyngeal bulb, but with the prosthesis removed (C3), and six months after the use of the pharyngeal bulb, but with the prosthesis in place (C4). Images of nasoendoscopic assessment of velopharyngeal function were obtained under all conditions were analyzed by speech-pathologists to identify the occurrence of Passavant's ridge during speech production. The results revealed a significant difference between molding condition (C2: 40%) and six months of bulb use (C4: 68%) (p = 0.028). The pharyngeal bulb may elicit the Passavant`s ridge in patients with history of cleft palate presenting with VPI.
Keywords: Cleft palate; Passavant's ridge; Pharyngeal bulb; Velopharyngeal dysfunction